Political philosophy a very short introduction - Miller, David 1946- (Oxford University Press, 2003)
This short text introduces readers to the concepts of political philosophy. It starts by explaining why the subject is important and how it tackles basic ethical questions such as, 'how should we live together in society?'
Includes bibliographical references and index
Keywords: Philosophie; Politische Wissenschaft; Political science / Philosophy; Politische Philosophie; Einführung